An investigation on kinematics and dynamics performance of a novel 3-PRC-compliant parallel micromanipulator. (July 2018) - Li, Xiang-Chun; Li, Yangmin; Ding, Bing-Xiao; Xu, Hong-Ye
This article proposes a 3-PRC compliant parallel micromanipulator with 3 degrees of freedom. The piezoelectric actuator is adopted to drive the mechanism, and to compensate the stroke of the piezoelectric actuator, a new type of secondary lever amplification mechanism is designed. The kinematics model of the 3-PRC parallel micromanipulation platform is derived using vector method, and the forward and inverse kinematics solutions of a 3-PRC parallel micromanipulation stage are emphatically analyzed and then the Jacobian matrix of kinematics model and workspace are derived. Finally, the dynamic model is established by Lagrange equation, and the natural frequency of the mechanism is calculated. The modal analysis is carried out using finite element method. The results showed that the mechanism has a favorable performance on kinematics and dynamics, and this micromanipulator can achieve micro/nano level motion with high accuracy.